Children’s song media’s influence on consumption vegetables and fruits in primary school children - Aprianty, Deris; Bachtiar, Agus; Nuraeni, Irma Nuraeni (Indonesian Journal of Multidisciplinary Science, 2024)
Indonesian people consume 173 grams of fruits and vegetables per day, below the World Health Organization's recommended 400 grams. 16.54% of children aged 5-9 years do not consume vegetables and fruit, with 73.79% consuming only 1-2 portions daily. Low consumption is linked to increased risk of chronic diseases. To increase awareness, a song policy called "Vegetables and Fruits are Rich in Benefits" is being implemented in Tasikmalaya City elementary schools. The research used qualitative methods, including Focus Group Discussion and Brainstorming, and found positive responses from informants. The plan is supported by adequate facilities and infrastructure in schools. Stakeholders and schools agree to commit to the song to increase children's knowledge and consumption of vegetables and fruits.